Method for manufacturing molded article, molded article, and flat wire
By using a specific combination and treatment method of fluorine-based resin and polyimide-based thermoplastic resin in the flat line, the problems of stress concentration during bending and deformation of the flat line and crack peeling of the coated material film are solved, and excellent adhesion and crack resistance are achieved.
Patent Information
- Application Number
- CN202380062100.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the application of flat lines, especially when bending and deforming, the melt-kneaded mixture of fluorine resin and polyimide thermoplastic resin is prone to problems such as stress concentration, cracks in the coating material film and peeling.
By combining the fluorine-based thermoplastic resin F with the polyimide-based thermoplastic resin P with a lower glass transition temperature ratio, the glass transition temperature difference ΔTg is set to be 75 to 175°C, and melted at a higher temperature, and then cooled at a cooling rate of 10°C/min or more to form a uniform dispersion state of the fluorine-based resin in the polyimide-based thermoplastic resin.
The adhesion between the molded object and the bonded body is significantly improved, and crack resistance is resistant to bending and deformation, thereby avoiding cracks and peeling of the coated material film.
Smart Images

Figure BDA0005285961100000161 
Figure BDA0005285961100000171
Abstract
Description
Technical Field
[0001] The present disclosure relates to a method for manufacturing a formed article, a formed article, and a flat wire. Background Art
[0002] Fluororesins have excellent heat resistance, flame retardancy, chemical resistance, weather resistance, non-adhesiveness, low friction, and low dielectric properties, and are used in a wide range of fields, including corrosion-resistant piping materials for chemical plants, plastic greenhouse materials for agriculture, mold release coating materials for kitchen appliances, and covering materials for electric wires.
[0003] Patent document 1 discloses a prepreg comprising reinforcing fibers and a matrix resin; the matrix resin contains a thermoplastic resin (excluding the fluororesin described below) and a melt-molded fluororesin having a melting point of 100 to 325° C. and having at least one functional group selected from a carbonyl group, a hydroxyl group, an epoxy group, and an isocyanate group; in a total of 100% by mass of the thermoplastic resin and the fluororesin, the proportion of the thermoplastic resin is more than 30% by mass and less than 99% by mass, and the proportion of the fluororesin is more than 1% by mass and less than 70% by mass.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2017 / 122735 Summary of the invention
[0007] Technical problem to be solved by the invention
[0008] In addition to the prepreg described in Patent Document 1, the melt-kneaded product of fluorine-based resin and other thermoplastic resins has a wide range of uses, for example, sometimes used in combination with polyimide-based thermoplastic resins that are excellent in mechanical properties, heat resistance, dimensional stability, chemical resistance, low water absorption, etc. as other thermoplastic resins. Examples of uses of the melt-kneaded product of fluorine-based resin and polyimide-based thermoplastic resin include insulating coating materials for flat wires.
[0009] Although the melt-kneaded product of fluorine resin and polyimide thermoplastic resin is excellent in the above-mentioned properties, it is still not enough. In particular, when the proportion of fluorine resin is small and the fluorine resin is dispersed in the polyimide thermoplastic resin, the properties are sometimes not fully exerted, and it is required to improve the performance. The inventors have found that when the melt-kneaded product of fluorine resin and polyimide thermoplastic resin is applied to a flat wire, when the flat wire is bent and deformed, stress is concentrated on the edge portion of the flat conductor as the core wire, and the coating film of the portion is prone to cracking. In addition, it was found that the coating film is easily peeled off from the cracked portion.
[0010] One embodiment of the present disclosure provides a method for producing a molded product in which a fluorine-based resin is dispersed in a polyimide-based thermoplastic resin and the molded product is excellent in adhesion to an adherend and crack resistance during bending deformation.
[0011] In one embodiment of the present disclosure, there is provided a molded product in which a fluorine-based resin is dispersed in a polyimide-based thermoplastic resin, and the molded product is excellent in adhesion to an adherend and crack resistance during bending deformation.
[0012] In one embodiment of the present disclosure, there is provided a flat wire having excellent adhesion between a flat conductor and a film of an insulating coating material and excellent crack resistance during bending deformation.
[0013] Technical solutions adopted to solve technical problems
[0014] The present invention has the following technical contents.
[0015] <1> A method for producing a molded product, wherein a composition comprising a polyimide-based thermoplastic resin P and a fluorine-based thermoplastic resin F having a lower glass transition temperature than the polyimide-based thermoplastic resin P, wherein the difference ΔTg between the glass transition temperature Tg-p of the polyimide-based thermoplastic resin P and the glass transition temperature Tg-f of the fluorine-based thermoplastic resin F is 75 to 175° C. is melted at a temperature higher than the melting point of the polyimide-based thermoplastic resin P or the melting point of the fluorine-based thermoplastic resin F to obtain a molten product,
[0016] The melt is cooled at a cooling rate of 10°C / min or more to obtain a molded product.
[0017] The fluorine-based thermoplastic resin F is dispersed in the polyimide-based thermoplastic resin P in the molded product.
[0018] <2> like <1> The method for manufacturing the formed product, wherein the glass transition temperature Tg-p is 150 to 250°C.
[0019] <3> like <1> or <2> In the method for producing a molded product, the mass ratio of the polyimide thermoplastic resin P / the fluorine thermoplastic resin F in the composition is 40 / 60 to 98 / 2.
[0020] <4> like <1> ~ <3> The method for producing a molded product according to any one of the above, wherein an average dispersed particle size of the fluorine-based thermoplastic resin F in the molded product is less than 10 μm.
[0021] <5> like <1> ~ <4> The method for producing a molded product according to any one of the above aspects, wherein the difference ΔTg is 75 to 125°C.
[0022] <6> like <1> ~ <5> The method for producing a molded product according to any one of the preceding claims, wherein the cooling rate is 50° C. / min or more.
[0023] <7> like <1> ~ <6> In the method for producing a molded product as described in any one of the above, the melting point of the polyimide-based thermoplastic resin P is 300°C or higher and lower than 420°C.
[0024] <8> like <1> ~ <7> The method for producing a molded product according to any one of the preceding claims, wherein the melting point of the fluorine-based thermoplastic resin F is 260 to 320°C.
[0025] <9> A molded product, comprising a polyimide thermoplastic resin P having a melting point of 300°C or more and less than 420°C and a fluorine-based thermoplastic resin F having a melting point of 260°C to 320°C, wherein the mass ratio of the polyimide thermoplastic resin P to the fluorine-based thermoplastic resin F is 40 / 60 to 98 / 2, and the fluorine-based thermoplastic resin F is dispersed in the polyimide thermoplastic resin P in a state where the average dispersed particle size is less than 10 μm.
[0026] <10> A flat wire comprises a flat conductor having a rectangular cross section in a direction perpendicular to an axial direction and a film of an insulating coating material covering the entire circumference of the flat conductor.
[0027] The insulating coating material comprises a polyimide thermoplastic resin P having a melting point of more than 300°C and less than 420°C and a fluorine thermoplastic resin F having a melting point of 260°C to 320°C, the mass ratio of the polyimide thermoplastic resin P to the fluorine thermoplastic resin F being 40 / 60 to 98 / 2, the fluorine thermoplastic resin F being dispersed in the polyimide thermoplastic resin P, and the average dispersed particle size of the fluorine thermoplastic resin F being less than 10 μm.
[0028] <11> like <10> In the flat wire, the average thickness of the film of the insulating coating material is 10 to 300 μm.
[0029] <12> like <10> or <11> The above-mentioned flat wire has an unbiased standard deviation of the thickness of the film of the insulating coating material in the axial direction of the flat wire of less than 0.06 mm.
[0030] <13> like <10> ~ <12> The flat wire according to any one of the preceding claims, wherein the insulating coating material has a bending stress of less than 140 MPa at 23°C.
[0031] <14> like <10> ~ <13> The flat wire according to any one of the preceding claims, wherein the cross-sectional area of the flat conductor is 2.6 mm 2above.
[0032] Effects of the Invention
[0033] According to one embodiment of the present disclosure, there is provided a method for producing a molded product in which a fluorine-based resin is dispersed in a polyimide-based thermoplastic resin and the molded product is excellent in adhesion to an adherend and crack resistance during bending deformation.
[0034] According to one embodiment of the present disclosure, there is provided a molded product in which a fluorine-based resin is dispersed in a polyimide-based thermoplastic resin, and the molded product is excellent in adhesion to an adherend and crack resistance during bending deformation.
[0035] Furthermore, according to one embodiment of the present disclosure, it is possible to provide a flat wire in which the flat conductor and the film of the insulating coating material are excellent in adhesion and crack resistance during bending deformation. DETAILED DESCRIPTION
[0036] The melting point is the temperature corresponding to the maximum of the melting peak measured by differential scanning calorimetry (DSC).
[0037] The cooling rate (°C / min) of the melt is a value obtained by dividing the difference between the temperature of the melt in the heating zone and the temperature of the melt measured within 30 seconds to 1 minute after being discharged from the heating zone by the time.
[0038] The "melt flow rate" is a melt flow rate (MFR) specified in JIS K 7210-1:2014 (corresponding to the international standard ISO 1133-1:2011). Hereinafter, the melt flow rate is also referred to as MFR.
[0039] The glass transition temperature is the temperature corresponding to the maximum value of the tan δ peak measured by the dynamic viscoelasticity measurement (DMA) method. Hereinafter, the glass transition temperature is also referred to as Tg.
[0040] The average dispersed particle size is obtained by observing the molded product or insulating coating material with a scanning electron microscope (SEM), measuring the maximum diameter of 100 randomly selected areas (dispersed particles), and taking the arithmetic average. The molded product or insulating coating material is sliced as needed to prepare a sample for SEM observation.
[0041] The average thickness of the insulating coating film was determined by taking a 5 m flat wire, measuring the thickness of the insulating coating film on the long side of a cross section perpendicular to the axial direction every 100 mm, and taking the arithmetic average.
[0042] The unbiased standard deviation of the thickness of the insulating coating material in the axial direction of the flat wire is obtained by measuring the thickness of the insulating coating material on the long side of a cross section perpendicular to the axial direction every 100 mm for 5 m of the flat wire and obtaining the measured values.
[0043] The bending stress is a value obtained by three-point bending (method A) specified in JIS K 7074: 1998. That is, at any time point in the bending test based on three-point bending, the product of the bending load applied to the test piece and the distance between the supporting points is divided by the square of the width and thickness of the test piece and multiplied by a coefficient.
[0044] The unit of a polymer refers to a portion (polymerized unit) derived from a monomer formed by polymerization of the monomer. A unit may be a unit directly formed by polymerization, or a unit in which a portion of the unit is converted into another structure by treating the polymer. In the present disclosure, a unit based on a monomer is also referred to as a monomer unit.
[0045] In the present disclosure, a numerical range expressed by "to" includes the numerical values described before and after "to" as a minimum value and a maximum value, respectively.
[0046] In the numerical ranges recorded in the present disclosure, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other classifications. In addition, in the numerical ranges recorded in the present disclosure, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiments.
[0047] In the present disclosure, each component may include a plurality of corresponding substances. When a plurality of substances corresponding to each component are present in the composition, unless otherwise specified, the content rate or content of each component refers to the total content rate or total content of the plurality of substances present in the composition.
[0048] [Method for producing molded product]
[0049] The method for producing a molded product disclosed in the present invention is a method for producing a molded product in which a fluorine-based thermoplastic resin F (hereinafter also referred to as "resin F") is dispersed in a polyimide-based thermoplastic resin P (hereinafter also referred to as "resin P"), which comprises melting a composition comprising the resin P and the resin F having a lower glass transition temperature than the resin P, wherein the difference ΔTg between the glass transition temperature Tg-p of the resin P and the glass transition temperature Tg-f of the resin F is 75 to 175°C at a temperature higher than the melting point of the resin P or the melting point of the resin F, to obtain a melt, and cooling the melt at a cooling rate of 10°C / min or more to obtain a molded product.
[0050] By adopting the above-mentioned production method, a molded product having excellent adhesion to an adherend and crack resistance during bending deformation can be obtained. The reason for this is not clear, but it is presumed as follows.
[0051] When the composition is melted at a temperature higher than the melting point of resin P or the melting point of resin F, whichever is higher, resin F, which occupies a smaller volume than resin P, flows in resin P and mixes with resin P to form a melt of both. In the subsequent cooling, resin P, which has a higher glass transition temperature than resin F, starts to solidify earlier than resin F, but at a temperature higher than the glass transition temperature of resin F, resin F still has flexibility, so resin F, which has low affinity with different materials, aggregates and becomes isolated, and is difficult to be densely dispersed in resin P. At this time, if the prescribed cooling conditions are met, aggregation of resin F in resin P is suppressed, and as a result, a molded product in which resin F is densely dispersed in resin P is easily formed. In particular, if the glass transition temperature difference ΔTg between resin P and resin F is within a prescribed range, a molded product in which resin F is densely dispersed in resin P can be easily and efficiently formed. As a result, it is estimated that the formed molded product can exhibit the above-mentioned characteristics.
[0052] The melt is obtained by melt-kneading resin P and resin F. At this time, other components can be added. As the device used for melt-kneading, known kneading machines (double-screw extruders, single-screw extruders, kneaders, mixers, etc.) can be cited. Among them, extruders are preferred, and double-screw extruders are particularly preferred.
[0053] The melt-kneading temperature may be a temperature higher than the melting point of the resin P or the melting point of the resin F, for example, preferably 260° C. or higher and lower than 450° C., more preferably 320 to 420° C. When the melt-kneading temperature is 260° C. or higher, the resin F is easily dispersed in the resin P during melt-kneading, and the average dispersed particle size of the resin F is easily less than 10 μm. When the melt-kneading temperature is lower than 450° C., it is easy to suppress the degradation of the resin P or the resin F caused by heat.
[0054] The residence time in the extruder is preferably 10 seconds to 30 minutes.
[0055] The screw speed of the extruder is preferably 50 to 2000 rpm.
[0056] The glass transition temperature Tg-f of resin F is lower than the glass transition temperature Tg-p of resin P, and the difference ΔTg between Tg-p and Tg-f is 75 to 175°C, preferably 75 to 160°C, more preferably 75 to 125°C, and further preferably 75 to 100°C.
[0057] The mass ratio of resin P / resin F is preferably 40 / 60 to 98 / 2, more preferably 50 / 50 to 98 / 2, further preferably 65 / 35 to 95 / 5, and particularly preferably 70 / 30 to 90 / 10.
[0058] When the mass ratio is 40 / 60 or more, that is, when the resin P is 40 parts by mass or more relative to 100 parts by mass of the total of the resin P and the resin F, the molded product has excellent adhesion to the adherend and the resin F is easily dispersed in the resin P. When the mass ratio is 98 / 2 or less, the bending stress of the molded product is low and the molded product has excellent crack resistance during bending deformation.
[0059] The obtained melt is cooled at a cooling rate of 10°C / min or more to obtain a molded product. The cooling rate at the start of cooling is preferably 20°C / min or more, more preferably 40°C / min or more, and further preferably 50°C / min or more. In addition, the cooling rate is preferably 200°C / min or less, more preferably 150°C / min or more. When the cooling rate is 200°C / min or less, the generation of cracks in the molded product tends to be suppressed.
[0060] Here, the start of cooling refers to the time point when the molded product is discharged outside the heating area, for example, when an extruder is used as a kneading machine, it refers to the time when the molded product is extruded from the outlet of the extruder. The cooling is preferably carried out at a rate of 10°C / min or more until the temperature of the molded product reaches at least the glass transition temperature Tg-f of the resin F. After cooling to a temperature below Tg-f, there is no particular restriction on the cooling rate.
[0061] Hereinafter, a method for producing a molded product will be described by taking a case where a molded product is produced using a melt extruder as an example.
[0062] Resin P, resin F and other components as needed are fed into the raw material inlet of the melt extrusion molding machine. The temperature during melt mixing of the melt extrusion molding machine is set to a temperature above the melting point of resin P or the melting point of resin F, whichever is higher. In the case where the die is installed downstream of the melt extrusion molding machine, the temperature of the die is also set to a temperature above the melting point of resin P or the melting point of resin F, whichever is higher. In addition, the cooling rate at the die outlet is set to more than 10°C / minute. An air cooler can be provided at the die outlet, and the cooling rate can be adjusted by using the air cooler. In addition, a heater can also be provided at the die outlet, and the cooling rate can be adjusted by using the air cooler and the heater.
[0063] When obtaining a sheet-shaped formed object, the pressing roller can be rotatably supported below the mold, and the cooling roller is slidably clamped between the pressing rollers. A plurality of cooling rollers can be configured. In addition, a winder for winding the sheet can be provided downstream.
[0064] In the obtained molded product, resin F is dispersed in resin P, and the average dispersed particle size of resin F is preferably less than 10 μm, more preferably 7 μm or less, and further preferably 5 μm or less. When the average dispersed particle size of resin F is less than 10 μm, crack resistance during bending deformation is excellent.
[0065] The lower limit of the average dispersed particle size of the resin F is not particularly limited, and is, for example, 0.01 μm.
[0066] The average dispersed particle size of the resin F can be adjusted by adjusting the mass ratio of the resin P / resin F, the kneading conditions, the cooling rate, and the like.
[0067] Hereinafter, materials used in the production method of the present disclosure will be described.
[0068] <Polyimide-based thermoplastic resin>
[0069] The resin P is a thermoplastic resin having an imide group in the main chain.
[0070] The resin P may, for example, be thermoplastic polyimide (hereinafter also referred to as "TPI"), polyetherimide or polyamideimide.
[0071] The glass transition temperature Tg-p of the resin P is preferably 150°C or higher, more preferably 170°C or higher, and further preferably 180°C or higher. The upper limit of Tg-p is, for example, 250°C or lower, and may be 200°C or lower.
[0072] The resin P may or may not have a melting point. From the viewpoint of wear resistance, the resin P preferably has a melting point.
[0073] The melting point of the resin P having a melting point is preferably 300° C. or higher, more preferably 320° C. or higher, and further preferably 340° C. or higher. When the melting point of the resin P is 300° C. or higher, the insulation coating material has excellent heat resistance and abrasion resistance.
[0074] The melting point of the resin P having a melting point is preferably lower than 420° C., more preferably lower than 415° C. When the melting point of the resin P is lower than 420° C., processability is excellent.
[0075] The above lower limit value and the above upper limit value may be combined as appropriate.
[0076] As an example of the resin P having a melting point of 300° C. or higher and lower than 420° C., thermoplastic polyimide (TPI) may be mentioned.
[0077] A commercially available resin or a resin produced by a known production method may be used as the resin P. Examples of commercially available TPI include Aurum (registered trademark) series produced by Mitsui Chemicals, Inc. and THERPLIM (registered trademark) series produced by Mitsubishi Gas Chemical Co., Ltd.
[0078] <Fluorine-based thermoplastic resin>
[0079] The glass transition temperature Tg-f of resin F is lower than the glass transition temperature Tg-p of resin P, and the difference ΔTg from Tg-p can be 75°C to 175°C, for example, preferably 75°C or higher, more preferably 80°C or higher. In addition, the upper limit of Tg-f is, for example, 175°C or lower, 150°C or lower, 120°C or lower, or 100°C or lower.
[0080] The above lower limit value and the above upper limit value may be combined as appropriate.
[0081] The melting point of the resin F is preferably 260° C. or higher, more preferably 270° C. or higher, and further preferably 280° C. or higher. When the melting point of the resin F is 260° C. or higher, the wear resistance is excellent.
[0082] The melting point of the resin F is preferably 380° C. or lower, more preferably 340° C. or lower, and further preferably 320° C. or lower. When the melting point of the resin F is 380° C. or lower, the resin F can be easily dispersed in the resin P.
[0083] The above lower limit value and the above upper limit value may be combined as appropriate.
[0084] The resin F preferably has at least one functional group selected from the group consisting of a carbonyl group, a hydroxyl group, an epoxy group, and an isocyanate group. The resin F can be easily dispersed in the resin P by having a functional group.
[0085] The functional group is preferably present as either or both of a terminal group of the main chain of the resin F and a pendant group of the main chain.
[0086] As the functional group, from the viewpoint of dispersibility in the resin P, a carbonyl-containing group is preferred.
[0087] The carbonyl-containing group is a group having a carbonyl group (-C(=O)-) in its structure. Examples of the carbonyl-containing group include groups having a carbonyl group between carbon atoms of a hydrocarbon group, carbonate groups, carboxyl groups, haloformyl groups, alkoxycarbonyl groups, and acid anhydride groups.
[0088] Examples of the hydrocarbon group in the group having a carbonyl group between carbon atoms of the hydrocarbon group include an alkylene group having 2 to 8 carbon atoms. The carbon number of the alkylene group is the number of carbon atoms excluding the carbon atoms constituting the carbonyl group. The alkylene group may be linear or branched.
[0089] The haloformyl group is represented by -C(=O)-X (wherein X is a halogen atom). Examples of the halogen atom in the haloformyl group include a fluorine atom and a chlorine atom, and a fluorine atom is preferred. That is, the haloformyl group is preferably a fluoroformyl group (also referred to as a carbonyl fluoride group).
[0090] The alkoxy group in the alkoxycarbonyl group is preferably an alkoxy group having 1 to 8 carbon atoms, and particularly preferably a methoxy group or an ethoxy group. The alkoxy group may be linear or branched.
[0091] The content of functional groups in fluororesin is 1×10 6 The number is preferably 10 to 60,000, more preferably 100 to 50,000, further preferably 100 to 10,000, and particularly preferably 300 to 5000. When the content of the functional group is at least the above lower limit, the dispersibility is excellent, and when it is at most the above upper limit, the thermal stability is excellent.
[0092] The content of the functional group can be measured by nuclear magnetic resonance (NMR) analysis, infrared absorption spectrum analysis, etc. For example, by using infrared absorption spectrum analysis as described in Japanese Patent Application Laid-Open No. 2007-314720, the content of the functional group can be calculated by finding the ratio (mol %) of units having functional groups in all units constituting the fluororesin and then calculating the content of the functional group from the ratio.
[0093] As resin F, for example, there can be exemplified a fluoropolymer having at least one of a unit containing a functional group and a terminal group containing a functional group. As fluoropolymer, for example, there can be exemplified a fluorinated copolymer (hereinafter referred to as "PFA") with tetrafluoroethylene (hereinafter referred to as "TFE") unit and perfluoro (alkyl vinyl ether) (hereinafter referred to as "PAVE") unit, a fluorinated copolymer (hereinafter referred to as "FEP") with TFE unit and hexafluoropropylene (hereinafter referred to as "HFP") unit, a fluorinated copolymer with TFE unit and ethylene unit, a fluorinated copolymer with vinylidene fluoride unit, a fluorinated copolymer with chlorotrifluoroethylene (hereinafter referred to as "CTFE") unit, a fluorinated copolymer with ethylene unit and CTFE unit. Wherein, from the viewpoint of electrical properties (dielectric constant, dielectric loss tangent) and heat resistance, preferably PFA, FEP, particularly preferably PFA.
[0094] <Other ingredients>
[0095] The molded product may contain other components. Examples of other components include fillers, pigments, and other additives.
[0096] Specific examples of fillers include fibrous fillers such as glass fiber, carbon fiber, boron fiber, aramid fiber, liquid crystal polyester fiber, stainless steel microfiber, and powdered fillers such as talc, mica, graphite, molybdenum disulfide, polytetrafluoroethylene, calcium carbonate, silica, silica-alumina, alumina, and titanium dioxide. In addition, hydrotalcites and metal oxides such as zinc oxide, magnesium oxide, titanium oxide, and lead oxide can be mentioned. One or more inorganic fillers can be used.
[0097] Examples of the pigment include coloring pigments such as organic pigments and inorganic pigments, and specific examples include carbon black (black pigment), iron oxide (red pigment), aluminum cobalt oxide (blue pigment), copper phthalocyanine (blue pigment, green pigment), perylene (red pigment), and bismuth vanadate (yellow pigment).
[0098] The total content of the resin P and the resin F is preferably 50% by mass or more, more preferably 70% by mass or more, and may be 100% by mass, based on the total mass of the molded product.
[0099] [Molded article]
[0100] A molded product according to one embodiment of the present disclosure comprises a polyimide thermoplastic resin P having a melting point of 300°C or higher and lower than 420°C and a fluorine-based thermoplastic resin F having a melting point of 260°C to 320°C, wherein the mass ratio of the resin P to the resin F is 40 / 60 to 98 / 2, and the resin F is dispersed in the resin P in a state where the average dispersed particle size is less than 10 μm.
[0101] In addition, the molded product of other embodiments of the present disclosure includes a polyimide thermoplastic resin P and a fluorine-based thermoplastic resin F having a lower glass transition temperature than the above-mentioned polyimide thermoplastic resin P, the difference ΔTg between the glass transition temperature Tg-p of the above-mentioned polyimide thermoplastic resin P and the glass transition temperature Tg-f of the above-mentioned fluorine-based thermoplastic resin F is 75 to 175°C, the mass ratio of the above-mentioned polyimide thermoplastic resin P / the above-mentioned fluorine-based thermoplastic resin F is 40 / 60 to 98 / 2, and the above-mentioned fluorine-based thermoplastic resin F is dispersed in the above-mentioned polyimide thermoplastic resin P in a state where the average dispersed particle size is less than 10μm.
[0102] By making the molded product of the above-mentioned structure, the crack resistance during the adhesion and bending deformation of the adherend is excellent. For resin P and resin F, the meanings described in the manufacturing method of the molded product are the same, and other parts can also be referred to. The molded product of the above-mentioned structure can be obtained by the manufacturing method of the above-mentioned molded product.
[0103] [Flat Line]
[0104] The flat wire of the present disclosure includes a flat conductor having a rectangular cross section in a direction perpendicular to an axial direction and a film of an insulating coating material covering the entire circumference of the flat conductor.
[0105] (Flat conductor)
[0106] The flat conductor is a core wire of a flat wire and is a conductor having a rectangular cross section in a direction perpendicular to the axial direction.
[0107] The material of the rectangular conductor may be a material known as a core wire of an electric wire, and examples thereof include copper, tin, silver, gold, aluminum, and alloys thereof. Among them, copper is preferred from the viewpoint of easy formation of the rectangular conductor.
[0108] The thickness of the rectangular conductor is, for example, 0.5 to 3.0 mm.
[0109] The width of the rectangular conductor is, for example, 1.0 to 5.0 mm.
[0110] The cross-sectional area of the flat conductor is preferably 2.6 mm 2 More preferably 3.0 mm 2 The upper limit of the cross-sectional area of the rectangular conductor is not particularly limited, but is, for example, 15 mm 2 .
[0111] The cross-sectional area of the flat conductor is the cross-sectional area in a direction perpendicular to the axial direction.
[0112] When the adhesion between the rectangular conductor and the film of the insulating coating material is weak, the larger the cross-sectional area of the rectangular conductor, the easier it is for the film of the rectangular conductor and the insulating coating material to peel off. The insulating coating material of this embodiment has excellent adhesion with the rectangular conductor, so the larger the cross-sectional area of the rectangular conductor, the higher the usefulness.
[0113] (Insulation coating material)
[0114] The insulating coating material comprises a polyimide thermoplastic resin P having a melting point of 300°C or higher and lower than 420°C and a fluorine thermoplastic resin F having a melting point of 260°C to 320°C, wherein the mass ratio of the resin P to the resin F is 40 / 60 to 98 / 2, the resin F is dispersed in the resin P, and the average dispersed particle size of the resin F is less than 10 μm.
[0115] The resin P and the resin F have the same meanings as those described in the method for producing a molded product, and the same may be said for other parts.
[0116] The bending stress of the insulating coating material at 23° C. is preferably less than 140 MPa, preferably 135 MPa or less, and more preferably 125 MPa or less. When the bending stress is less than 140 MPa, crack resistance during bending deformation is excellent.
[0117] The insulating coating material preferably has a bending stress of 90 MPa or more, more preferably 100 MPa or more at 23° C. When the bending stress is 100 MPa or more, the wear resistance is excellent.
[0118] The above lower limit value and the above upper limit value may be combined as appropriate.
[0119] The bending stress can be adjusted by adjusting the bending stress of the resin P itself, the mass ratio of the resin P / resin F, the kneading conditions, and the like.
[0120] The MFR of the insulating coating material at 400° C. and 5 kgf is preferably 5 to 200 g / 10 minutes, more preferably 20 to 90 g / 10 minutes, and further preferably 30 to 80 g / 10 minutes.
[0121] (Film of insulation coating material)
[0122] The average thickness of the film of the insulating coating material is preferably 10 μm or more, more preferably 50 μm or more, and further preferably 100 μm or more. When the average thickness of the film is 10 μm or more, excellent tracking resistance is achieved.
[0123] The average thickness of the film of the insulating coating material is preferably 300 μm or less, more preferably 250 μm or less, and further preferably 200 μm or less. When the average thickness of the film is 300 μm or less, the overall thickness of the flat wire can be reduced, and when it is made into a coil, the space of the entire coil can be saved, which helps to miniaturize the electrical device.
[0124] The above lower limit value and the above upper limit value may be combined as appropriate.
[0125] The unbiased standard deviation of the film thickness of the insulating coating material in the axial direction of the flat wire (hereinafter also referred to as "thickness variation") is preferably less than 0.06 mm, more preferably less than 0.03 mm, and further preferably less than 0.01 mm. When the thickness variation of the film is less than 0.06, the crack resistance and tracking resistance during bending deformation are excellent.
[0126] The smaller the variation in thickness of the film, the better, and it may be 0. From the viewpoint of ease of production and yield, the variation in thickness of the film is preferably 0.001 mm or more.
[0127] In the flat wire, another layer may be present between the flat conductor and the film of the insulating coating material. Examples of the other layer include a primer layer.
[0128] In the present disclosure, the rectangular conductor and the film of the insulating coating material are in good contact with each other even without the interposition of the primer layer, and therefore, it is preferred that the rectangular conductor and the film of the insulating coating material are in direct contact with each other.
[0129] (Method for producing flat wire)
[0130] The rectangular wire can be produced, for example, by forming a film of an insulating coating material on a rectangular conductor so as to cover the entire circumference of the rectangular conductor.
[0131] As a molding method, a method of melting the insulating coating material using an extruder equipped with a die and extruding the molten insulating coating material from the die around the rectangular conductor is preferred because the thickness variation of the insulating coating film is small.
[0132] The barrel temperature and die temperature of the extruder are preferably 260° C. or higher and lower than 450° C., more preferably 320 to 420° C. The cooling rate at the die outlet is preferably 10° C. / min or higher, more preferably 20° C. / min or higher, further preferably 40° C. / min or higher, particularly preferably 50° C. / min or higher.
[0133] (Application of flat wire)
[0134] The flat wire of the present disclosure can be applied to, for example, insulating amplifiers, insulating transformers, automotive alternators, hybrid vehicles, electric ships, electric aircraft, electric vertical take-off and landing aircraft motors, etc. In addition, it can also be used as various electric wires (winding wires, automotive wires, robot wires), coil windings (electromagnetic wires).
[0135] Example
[0136] The present disclosure is described in more detail below using examples, but the present disclosure is not limited to these examples. In the following examples, Examples 1 to 56, 10, and 11 are examples, and Examples 67 to 9, and 12 to 14 are comparative examples. "Parts" means "parts by mass".
[0137] (Evaluation method)
[0138] <Bending stress of insulation coating material>
[0139] The insulating coating material was molded into a test piece specified in JIS K 7074: 1988 by injection molding. The obtained test piece was subjected to a bending test based on three-point bending (A method) in accordance with JIS K 7074: 1988 under the conditions of 23±2°C, 50±5%RH, 4cm between support points, 1mm / min test speed, and 1t (10%) load cell to obtain the bending stress.
[0140] <MFR of insulation coating material>
[0141] After preheating the insulating coating material for 5 minutes, the MFR at 400° C. and 5 kgf was measured in accordance with JIS K 7210-1:2014.
[0142] <Average Dispersed Particle Size>
[0143] The particles are sliced to prepare an observation sample, the observation sample is observed with a scanning electron microscope (SEM), the maximum diameters of 100 randomly selected regions (dispersed particles) are measured, and the arithmetic mean is taken as the average dispersed particle diameter.
[0144] The insulating coating material is observed with a scanning electron microscope (SEM), and the maximum diameters of 100 randomly selected regions (dispersed particles) are measured, and the arithmetic mean is taken as the average dispersed particle size.
[0145] <Average thickness and thickness variation of the film>
[0146] A 5-m long flat wire was taken and the thickness of the insulating coating material film on the long side of the cross section perpendicular to the axial direction was measured every 100 mm (only the side in contact with the upper inner surface of the die during molding).
[0147] The arithmetic mean of the measured values (mm) was defined as the average thickness.
[0148] The unbiased standard deviation (mm) of the measured values (mm) was taken as the thickness variation.
[0149] <Crack resistance when bending>
[0150] The flat wire was subjected to bending deformation in the edgewise direction and the flatwise direction. The deformation angle was 90±10°. After that, the film was visually observed and the crack resistance was evaluated according to the following criteria.
[0151] A: No cracks occurred even after deformation 10 times.
[0152] B: Cracks occurred after deformation 10 times.
[0153] C: Cracks occurred at 5 times of deformation, but no peeling occurred.
[0154] D: Cracks occurred at 5 times of deformation, and peeling also occurred.
[0155] <Adhesion when bending>
[0156] The flat wire was subjected to bending deformation in the edgewise direction and the flatwise direction. The deformation angle was 90±10°. The cross section of the bent and deformed portion was then visually observed and the adhesion was evaluated according to the following criteria.
[0157] A: Even after being bent 10 times, the film of the insulating coating material did not float up from the conductor during bending, and no space was generated between the film of the insulating coating material and the conductor.
[0158] B: After being bent 10 times, the film of the insulating coating material floated up from the conductor during bending, and a space was generated between the film of the insulating coating material and the conductor.
[0159] C: When bent five times, the film of the insulating coating material floated up from the conductor during the bending, and a space was generated between the film of the insulating coating material and the conductor.
[0160] (Materials used)
[0161] TPI-1: thermoplastic polyimide, glass transition temperature Tg-p = 250°C, melting point = 390°C, true specific gravity = 1.33, "Aurum PD500" manufactured by Mitsui Chemicals, Inc.
[0162] TPI-2: thermoplastic polyimide, glass transition temperature Tg-p = 185°C, melting point = 320°C, true specific gravity = 1.29, "THERPLIM TO65" manufactured by Mitsubishi Gas Chemical Co., Ltd.
[0163] Fluororesin-1: TFE / Norbornene anhydride / CF 2 =CFOCF 2 CF 2 CF 3 =97.9 / 0.1 / 2 (molar ratio) of the fluorine-containing copolymer, melting point = 310°C, glass transition temperature Tg-f = 90°C, true specific gravity = 2.17.
[0164] Fluororesin-2: A fluorine-containing copolymer comprising TFE / ethylene / butene / itaconic anhydride, melting point = 190°C, glass transition temperature Tg-f = 50°C, true specific gravity = 2.14.
[0165] (Examples 1 to 7)
[0166] <Manufacture of insulating coating materials>
[0167] TPI-1 and fluororesin-1 were dry-mixed in the proportions (parts) shown in Table 1, and fed into a twin-screw extruder (manufactured by Technovel Co., Ltd., KZW15TW-45MG), and melt-kneaded under the conditions of resin discharge rate: 2 kg / hour, screw speed: 400 rpm, and set die temperature: 395°C to obtain a granular insulating coating material. In addition, the die outlet was air-cooled so that the cooling rate at the start of cooling was 50°C / minute.
[0168] <Production of flat wire>
[0169] Using the obtained insulating covering material, electric wire extrusion molding was performed under the following conditions to obtain a flat wire.
[0170] Die temperature: 400℃.
[0171] Barrel temperature: 370~400℃.
[0172] Flat conductor: Flat copper wire with a height of 1.5 mm and a width of 2.3 mm.
[0173] Coating thickness (set value): 0.15mm.
[0174] Cooling rate at the start of cooling: 50°C / min.
[0175] (Example 8)
[0176] Insulation coating materials were produced in the same manner as in Examples 1 to 7 except that fluororesin-1 was not used, thereby obtaining flat wires.
[0177] (Example 9)
[0178] The insulating coating material obtained in Example 3 was further pulverized using a freeze pulverizer TPH-01 manufactured by Azwan Co., Ltd. to obtain a powder of the insulating coating material.
[0179] The obtained powder was fed onto a flat conductor similar to that used in Examples 1 to 7 using a vibrating feeder, and then extruded to obtain a flat wire.
[0180] The above-mentioned evaluation was performed on the insulating coating material and the flat wire of each example. The results are shown in Table 1.
[0181] In addition, in Example 9, the bending stress was not measured, and since the fluororesin was not dispersed in TPI, the average dispersed particle size could not be measured.
[0182] [Table 1]
[0183]
[0184] (Examples 10~14)
[0185] Insulation coating materials were produced in the same manner as in Examples 1 to 7, except that TPI-1 or TPI-2 and fluororesin-1 or fluororesin-2 were used in the ratio (parts) shown in Table 2 and the cooling rate at the start of cooling was set to the conditions shown in Table 2 to obtain flat wires.
[0186] [Table 2]
[0187]
[0188] Examples 10 and 14 were excellent in crack resistance during bending and adhesion during bending. In particular, Example 10 was evaluated as A in both crack resistance during bending and adhesion during bending.
[0189] In addition, in Example 10, the MFR at 372°C and 5kgf is 22 g / 10 minutes, the tensile elongation is 21.2%, the tensile modulus is 892.9 MPa, the tensile strength is 19.98 MPa, the dielectric constant (10 GHz) is 2.16, the dielectric loss tangent (10 GHz) is 0.001, the dielectric constant (1 MHz) is 2.02, and the bending stress is 3 MPa.
[0190] The tensile elongation, tensile modulus and tensile strength were measured in accordance with JIS K7127:1999 under an environment of 23° C. and 50% RH at a tensile speed of 50 mm / min.
[0191] The dielectric constant and dielectric loss tangent were determined by the cavity perturbation method.
[0192] The adhesiveness when bent in Example 11 was excellent, the crack resistance when bent was poor in Ratios 1 to 5, 10, and 14, but excellent in Ratios 7 to 9, 12, and 13.
[0193] In Example 12, natural cooling was performed, so the cooling rate was lower than 10° C. / min, and the crack resistance during bending and the adhesion during bending were both poor.
[0194] In Example 13, since the glass transition temperature difference ΔTg exceeded 175° C., both the crack resistance during bending and the adhesion during bending were poor.
Claims
1. A method for producing a formed article, wherein: A composition comprising a polyimide-based thermoplastic resin P and a fluorine-based thermoplastic resin F having a lower glass transition temperature than the polyimide-based thermoplastic resin P, wherein the difference ΔTg between the glass transition temperature Tg-p of the polyimide-based thermoplastic resin P and the glass transition temperature Tg-f of the fluorine-based thermoplastic resin F is 75 to 175° C. is melted at a temperature higher than the melting point of the polyimide-based thermoplastic resin P or the melting point of the fluorine-based thermoplastic resin F to obtain a molten material, The melt is cooled at a cooling rate of 10°C / min or more to obtain a molded product. The fluorine-based thermoplastic resin F is dispersed in the polyimide-based thermoplastic resin P in the molded product.
2. The method for producing a molded product according to claim 1, wherein: The glass transition temperature Tg-p is 150-250°C.
3. The method for producing a molded product according to claim 1 or 2, wherein: The mass ratio of the polyimide-based thermoplastic resin P / the fluorine-based thermoplastic resin F in the composition is 40 / 60 to 98 / 2.
4. The method for producing a molded product according to claim 1 or 2, wherein: The average dispersed particle size of the fluorine-based thermoplastic resin F in the molded product is less than 10 μm.
5. The method for producing a molded product according to claim 1 or 2, wherein: The difference ΔTg is 75 to 125°C.
6. The method for producing a molded product according to claim 1 or 2, wherein: The cooling rate is above 50°C / min.
7. The method for producing a molded product according to claim 1 or 2, wherein: The melting point of the polyimide-based thermoplastic resin P is greater than or equal to 300° C. and less than 420° C.
8. The method for producing a molded product according to claim 1 or 2, wherein: The melting point of the fluorine-based thermoplastic resin F is 260-320°C.
9. A molded product comprising a polyimide thermoplastic resin P having a melting point of 300°C or higher and lower than 420°C and a fluorine-based thermoplastic resin F having a melting point of 260°C to 320°C, wherein the mass ratio of the polyimide thermoplastic resin P to the fluorine-based thermoplastic resin F is 40 / 60 to 98 / 2, and the fluorine-based thermoplastic resin F is dispersed in the polyimide thermoplastic resin P in a state where the average dispersed particle size is less than 10 μm.
10. A flat wire comprising a flat conductor having a rectangular cross section in a direction perpendicular to an axial direction and a film of an insulating coating material covering the entire circumference of the flat conductor, The insulating coating material comprises a polyimide thermoplastic resin P having a melting point of more than 300°C and less than 420°C and a fluorine thermoplastic resin F having a melting point of 260°C to 320°C, the mass ratio of the polyimide thermoplastic resin P to the fluorine thermoplastic resin F being 40 / 60 to 98 / 2, the fluorine thermoplastic resin F being dispersed in the polyimide thermoplastic resin P, and the average dispersed particle size of the fluorine thermoplastic resin F being less than 10 μm.
11. The flat wire according to claim 10, wherein The average thickness of the film of the insulating coating material is 10 to 300 μm.
12. The flat wire according to claim 10 or 11, wherein The unbiased standard deviation of the thickness of the film of the insulating coating material in the axial direction of the flat wire is less than 0.06 mm.
13. The flat wire according to claim 10 or 11, wherein The insulating coating material has a bending stress of less than 140 MPa at 23°C.
14. The flat wire according to claim 10 or 11, wherein The cross-sectional area of the flat conductor is 2.6 mm 2 above.
Citation Information
Patent Citations
Glass fiber-reinforced composite material, method of manufacturing the same, and printed circuit board
JP2007314720A
Prepreg, method for producing same, and fiber-reinforced molded product
WO2017122735A1